Social and ethnic segregation amongst the smallest Hungarian villages - Balogh, András; Bajmócy, Péter; Ilcsikné Makra, Zsófia (Geographica Pannonica, 2018)
Social segregation is one of the most important social problems in Central-Eastern Europe not only in urban, but also rural areas. The social segregation usually coexists with ethnic segregation. In Western-Europe we can see segregation mainly in towns, but in Eastern-Europe also in villages, usually connecting with Roma people. In the last decades number of population of small villages dropped dramatically and in some regions the most disadvantaged social groups appeared in these villages. Nowadays some of these villages have geographical, social and ethnic disadvantages together. To stop marginalization of people living in poverty is one of the biggest challenges nowadays in Hungary. According to the definition of Hungarian Statistical Office the whole settlement is regarded segregated if it has less than 200 inhabitants, therefore we also determined this limit. These settlements with population below 200 were the subject of this study. A complex indicator system was established containing six indicators (educational level, unemployment, comfort level of homes, etc.) These indicators served as the base of cluster analysis using the K-means algorithm resulted in five clusters. The 58 segregated settlements can be found mainly in peripheral areas of Northeastern- and Southwestern-Hungary. The proportion of Roma population is high in most of the segregated settlements. The aim of the paper is to describe the most important social problems of the smallest Hungarian villages, to find the groups of villages with social segregation and marginalization and to find context between marginalization, social and ethnic segregation amongst the tiny Hungarian villages.